(untitled) (Studia austriaca, 2013)
By now diverse movements of the 1960s such as the «Viennese Actionism» and predecessors (in the broadest sense) like the «literarische cabarets» of the so called «Wiener Gruppe» in 1958/59 are well documented and established in Austria’s cultural history. Other groups, art performances and happenings seem to be of marginal historical significance, probably because no chronicler has defined their sphere of influence. This essay investigates action theatre groups, happenings and similar movements initiated by the Austrian poets Wolfgang Bauer and Joe Berger in the 1960s and 1970s and points out their historical relevance.